Robust Kinetics of RNA Virus: Transcription Rates Are Set by Genome Levels - Timm, Collin (Biotechnol Bioeng, 2015)
In order to persist in nature, RNA viruses have evolved strategies to grow in diverse host environments. To better understand how such strategies might work, we used qRT-PCR to measure viral RNA species during cellular infections by a model RNA virus, vesicular stomatitis virus (VSV). Absolute levels of the VSV major transcript and genome were measured for infections in BHK and PC3 cells, across different multiplicities of infection (MOI 1, 10, 100), in the absence or presence of protein synthesis, as well as in cells in an interferon-activated anti-viral state. While viral genome replication was delayed in more resistant host cells, kinetic modeling of these data revealed a simple linear relationship between the mRNA production rate and genome levels under all tested conditions. These results indicate that while viral transcription and genome replication both depend on the availability of the viral RNA-dependent RNA polymerase and host cellular resources, transcription proceeds without apparent limits on these resources.